IDENTIFICATION OF CORAL REEF FISHES IN THE NATIONAL CONSERVATION AREA, ANAMBAS ISLAND, KEPULAUAN RIAU PROVINCE - Lisvina '; Chaidir P. Pulungan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The Anambas archipelago is consist of several islands and there are many coral fish species present in the Anambas waters. Information on types and population of coral fish in that area, however, is limited. To understand the type of coral fish present in the Anambas waters, a study has been conducted from April to June 2015. There were 5 sampling sites, namely the Temawan, Pasir Manang, Arung Hijau, Biang Matak and Nawan Islands. Fish catching was done by using scoop nets and line fishings. Fish sampled were then identified based on Allen, et al (2003) and Kuiter and Tonozuka (2001). Results shown that the coral fish caught were belonged to 3 orders, 18 families, 34 genera and 53 species. The most common fish present were the member of Lutjanidae, Siganidae and Serranidae, there were L. decussatus, L. fulviflamma, L. sebae, C. boenak, S. puellus, S. spinus, S. virgatus, S. vulvinus and A. stellatus.Keyword: Coral fish, Anambas island, Kepulauan Riau